RTPrimerDB: the Real-Time PCR primer and probe database - Pattyn, Filip (Oxford University Press, 2003)
The real-time polymerase chain reaction (PCR) methodology has become increasingly popular for nucleic acids detection and/or quantification. As primer/probe design and experimental evaluation is time-consuming, we developed a public database application for the storage and retrieval of validated real-time PCR primer and probe sequence records. The integrity and accuracy of the data are maintained by linking to and querying other reference databases. RTPrimerDB provides free public access through the Web to perform queries and submit user based information. Primer/probe records can be searched for by official gene symbol, nucleotide sequence, type of application, detection chemistry, LocusLink or Single Nucleotide Polymorphism (SNP) identifier, and submitter's name. Each record is directly linked to LocusLink, dbSNP and/or PubMed to retrieve additional information on the gene/SNP for which the primers/probes are designed. Currently, the database contains primer/probe records for human, mouse, rat, fruit fly and zebrafish, and all current detection chemistries such as intercalating dyes (SYBR Green I), hydrolysis probes (Taqman), adjacent hybridizations probes and molecular beacons. Real-time PCR primer/probe records are available at http://www.realtimeprimerdatabase.ht.st.